A novel mesenchymal‐associated transcriptomic signature for risk‐stratification and therapeutic response prediction in colorectal cancer. Issue 11 (13th July 2020) - Matsuyama, Takatoshi; Kandimalla, Raju; Ishikawa, Toshiaki; Takahashi, Naoki; Yamada, Yasuhide; Yasuno, Masamichi; Kinugasa, Yusuke; Hansen, Torben Frøstrup; Fakih, Marwan; Uetake, Hiroyuki; Győrffy, Balázs; Goel, Ajay
Abstract: Risk stratification in Stage II and III colorectal cancer (CRC) patients is critical, as it allows patient selection for adjuvant chemotherapy. In view of the inadequacy of current clinicopathological features for risk‐stratification, we undertook a systematic and comprehensive biomarker discovery effort to develop a risk‐assessment signature in CRC patients. The biomarker discovery phase examined 853 CRC patients, and identified a gene signature for predicting recurrence‐free survival (RFS). This signature was validated in a meta‐analysis of 1212 patients from nine independent datasets, and its performance was compared against established prognostic signatures and consensus molecular subtypes (CMS). In addition, a risk‐prediction model was trained (n = 142), and subsequently validated in an independent clinical cohort (n = 286). As a result, this mesenchymal‐associated transcriptomic signature (MATS) identified high‐risk CRC patients with poor RFS in the discovery (hazard ratio [HR]: 1.79), and nine validation cohorts (HR: 1.86). In multivariate analysis, MATS was the most significant predictor of RFS compared to established prognostic signatures and CMS subtypes. Intriguingly, MATS robustly identified CMS4‐subtype in multiple CRC cohorts (AUC = 0.92‐0.99). In the two clinical cohorts, MATS stratified low and high‐risk groups with a 5‐year RFS in the training (HR: 4.11) and validation cohorts (HR: 2.55), as well as predicted response to adjuvant therapy in Stage II and III CRC patients. We report a novel prognostic and predictive biomarker signature in CRC, which is superior to currently used approaches and have the potential for clinical translation in near future. Abstract : What's new? Numerous studies have tried to develop biomarkers or gene‐expression profiles to help predict which colorectal cancer (CRC) patients are most likely to benefit from adjuvant chemotherapies. In this study, the authors developed a "mesenchymal‐associated transcriptomic signature" (MATS) that was able to identify high‐risk CRC patients with poor recurrence‐free survival (RFS). In addition, the new MATS was able to predict the response of these patients to adjuvant therapy. Such biomarkers should lead to more appropriate risk stratification, and may improve survival outcomes in CRC patients.